Knowledge and Interests of Women of Childbearing Age (PUS) about Acetic Acid Visual Inspection (IVA) - Siti Komariyah; Lely Khulafa'ur Rosidah; Sucipto Sucipto; Heni Kristanto (Indonesian Journal of Global Health Research, 2023)
Reproductive health is a complete physical, mental and social condition, not only free from disease or disability in all aspects related to the reproductive system, its functions and processes. Cervical cancer is a primary malignant tumor originating from squamous epithelial cells, cancer that occurs in the cervix or cervix which is located between the uterus and the vaginal opening. Overcoming this problem requires efforts to solve the problem with other screening methods that are more capable, cost-effective and possible to be carried out in Indonesia. One of the alternative methods of cervical cancer screening that can answer these requirements is IVA (Visual Inspection with Acetic Acid Overlay). Women of Childbearing Age (PUS) about Acetic Acid Visual Inspection (IVA) In RW 05, Campurejo Village, Mojo Subdistrict, Kediri The research design used in this research is correlation research. The approach in this study uses a Cross Sectional approach. This research was conducted to find a relationship between the knowledge of Women of Childbearing Age (PUS) about Acetic Acid Visual Inspection (IVA) with an interest in Acetic Acid Visual Inspection (IVA).Results: Based on the results of the Spearman Rank test, P value = 0.007 <0.05 from a significant level of 5%, then H0 is rejected and H1 is accepted, meaning that there is a relationship between women's knowledge of IVA about IVA with interest in doing IVA in RW 05 Kelurahan Campurejo District City of Kediri. From results can be concluded that H1 is accepted, meaning that there is a relationship between knowledge of women of childbearing age (IVA) about Visual Inspection of Acetic Acid (IVA) with an interest in conducting Visual Inspection of Acetic Acid (IVA).